„Ma santé commence à être un peu meilleure...“ An Enlightener and his Health.: Part Two: Wenzel Anton of Kaunitz-Rietberg as a Patient (Theatrum historiae, 2021)
The second part of the two-part paper presents topics and sources viewed through the optics of Patienten- geschichte, concerning the relationship to health and illness of otherwise well-known Count and later Prince, Wenzel Anton of Kaunitz-Rietberg (1711–1794). Attention is paid to which methods and medicaments Kaunitz considered healthy, whether he followed any preventive treatment to maintain good health, and what he advised his relatives and friends. The paper also focuses on his cures, which medications he used and bought, how much he spent on and where he searched for them. Last but not least, the essay will try to find out Kaunitz’s sources of medical information, whether and how he reflected contemporary medical discourse, and if new findings and methods were somehow reflected in his approach to the illnesses and treatment that he and his relatives and friends underwent.
Keywords: aristocracy; early modern period; 18th century; enlightenment; Patientengeschichte; health and illness; medical treatment; medicaments; Wenzel Anton of Kaunitz-Rietberg